PAKU SEBAGAI IDE DALAM KARYA LUKISAN REALIS KONTEMPORER - Yulia Indra Sari, Yasrul Sami, S.Sn., M.Sn., Drs. Abd. Hafiz, M.Pd. (Serupa The Journal of Art Education, 2017)
This thesis aims to visualize spikes as depiction on social behavior that circulate around the community into a painting by contemporary realist style. Method creation of this work used multiple stages such as preparation, elaboration, synthesis, realization and completion of an exhibition concept and the final works. All the works are made to represent the work's title is lifted before. Works made communicating social behavior circulating around the community that leads to attitudes, behaviors and actions in daily life. Such as: 1) "Sharp", 2) "Melt", 3) "non-compliance", 4) "Time", 5) "Revenge", 6) "Forgiving", 7) "reply", 8) "Branch" , 9) "Dice", 10) "Umbrella". Each work is displayed telling about social behavior that circulates around the community in visualized in the form of spikes.Keywords: Paku, Social Behavior, Art, Contemporary Realist.